2016
DOI: 10.1177/0954405415616786
|View full text |Cite
|
Sign up to set email alerts
|

An ant colony approach to operation sequencing optimization in process planning

Abstract: Computer-aided process planning is an important component for linking design and manufacturing in computer-aided design/computer-aided process planning/computer-aided manufacturing integrated manufacturing systems. Operation sequencing in computer-aided process planning is one of the most essential tasks. To solve the problem and acquire optimal process plans, operation sequencing is modeled as a combinatorial optimization problem with various constraints, and a novel modified ant colony optimization algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In recent years, novel evolutionary or meta-heuristic algorithms have received wide applications. Hu et al [4] developed a hybrid ant colony algorithm to facilitate a feasible operation sequencing in process planning optimization with the objective of total weighted production cost reduction. More meta-heuristic algorithm based process planning optimization methods can be found in other existing publications.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, novel evolutionary or meta-heuristic algorithms have received wide applications. Hu et al [4] developed a hybrid ant colony algorithm to facilitate a feasible operation sequencing in process planning optimization with the objective of total weighted production cost reduction. More meta-heuristic algorithm based process planning optimization methods can be found in other existing publications.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, lots of investigations on process planning optimizations have been performed and some fruitful results are observed. For instance, Hu et al [4] suggested an ant colony algorithm in process planning to ensure feasible operation permutations. In general, existing publications regarding process planning optimization put more emphasis on obtaining an optimal process plan of a part with the minimum machining cost or the shortest machining time [5].…”
Section: Introductionmentioning
confidence: 99%
“…where a j j 2 + b j j 2 = 1. a j j 2 gives the probability that the Q-bit will be found in the ''0'' state, and b j j 2 gives the probability that the Q-bit will be found in the ''1'' state.…”
Section: Qieamentioning
confidence: 99%
“…Liu et al 19 considered one operation with several MRs. Then, the AC algorithm was used for OMS determination. Hu et al 20 also employed the AC algorithm for OMS optimization. They considered the machining rules and moved the ants by the OPG.…”
Section: Introductionmentioning
confidence: 99%